Calibration of the Numerical Model of a Stand in Dragão Stadium Based on Genetic Algorithms. Issue 2 (3rd April 2018) - Leite, Jorge; Ribeiro, Diogo; Marques, Hugo; Calçada, Rui
Abstract: This paper focuses on the experimental calibration of the numerical model of a stand in Dragão Stadium based on genetic algorithms. A finite-element numerical model was developed of a group of seating deck units including the connections between them and the connections with the stands. Dynamic tests were conducted on the seating decks in the north and south stands using an enhanced version of the frequency domain decomposition method (EFDD) in order to identify the local dynamic properties, namely the natural frequencies and modal configurations. Experimental calibration of the numerical model was performed using an iterative method based on a genetic algorithm. The stability of a significant number of parameters, considering different initial populations, proved the robustness of the adopted algorithm in the scope of the optimization of the numerical model. The calibration results demonstrate very good agreement between the numerical and experimental modal responses, showing a significant improvement on the numerical model before calibration. This resulted in a more effective connection between the seating deck units compared to the planned design and higher variability in the characteristics of the support conditions between the seating deck units and the stand beams, as evidenced by visual inspections carried out in situ .